Expectation Levels in Dictionary Consultation and Compilation - Kosch, Inge (Lexikos, 2013)
Dictionary consultation and compilation is a two-way engagement between two parties, namely a dictionary user and a lexicographer. How well users cope with looking up words in a Bantu language dictionary and to what extent their expectations are met, depends on their consultation skills, their knowledge of the structure of a Bantu language and the dictionary design. There are also demands that the lexicographer places on the user. These demands are of varying degrees, ranging from low-level expectations, where basic look-up skills according to the letters of the alphabet are assumed to have been mastered already (as needed when using a word-based dictionary), to medium-level expectations (such as being able to look up words in a stem-based dictionary), to high-level demands (where intuitive dictionary skills no longer suffice). A fine balance must be struck between the user's guidelines and the presumed dictionary consultation skill of the target user. This article endeavours to look into the matter of various levels of expectation of Bantu language dictionaries, both from the perspective of the user and the compiler.